Evaluasi Program Magang Guru di Dunia Industri Terhadap Peningkatan Kompetensi Profesional Guru Sekolah Menengah Kejuruan - Anwar Sadat; Ambiyar Ambiyar; Hasan Maksum (Pusdikra-Publishing.com, 2026)
Teacher internship programs in industry have become one of the strategic initiatives to strengthen the professional competence of vocational teachers and to enhance the relevance of vocational education to the needs of business and industry. However, evidence regarding the effectiveness of these programs remains limited, particularly in terms of their influence on teachers' professional practices and educational outcomes. This study aimed to evaluate the effectiveness of the teacher internship program implemented at SMK Negeri 1 Pariaman using the four-level Kirkpatrick Evaluation Model, namely Reaction, Learning, Behavior, and Results. A descriptive evaluative approach was employed involving all productive teachers who had participated in industrial internships during the previous three years through a total sampling technique. Data were collected using validated questionnaires, supported by document analysis, and analyzed through descriptive statistics using mean scores and percentages. The findings indicate that the overall effectiveness of the program was categorized as good, with an average score of 4.02 (80.40%). The highest achievement was found at the Reaction level (4.32; 86.40%), followed by Learning (4.15; 83.00%), Behavior (3.87; 77.40%), and Results (3.74; 74.80%). The internship program successfully enhanced teachers' industrial knowledge, technical competencies, and instructional practices. Nevertheless, the implementation of acquired competencies in classrooms was constrained by limited facilities and institutional support. These findings highlight the importance of continuous follow-up, stronger school–industry partnerships, and systematic evaluation to maximize the long-term impact of teacher internship programs on vocational education quality.